Functional Investigation of Meningeal Lymphatic System in Experimental Intracerebral Hemorrhage - Tsai, Hsin-Hsi; Hsieh, Yung-Chia; Lin, Jhih Syuan; Kuo, Zi-Ting; Ho, Chi-Ying; Chen, Chih-Hung; Chang, Che-Feng (Stroke (1970), 2022)
Promotion of hematoma resolution in a timely manner reduces intracerebral hemorrhage (ICH) brain injury induced by toxic blood components and subsequent neuroinflammation. The meningeal lymphatic system is responsible for clearance of macromolecules and pathogenic substances from the central nervous system; however, its role in intraparenchymal hematoma clearance and ICH outcomes is unknown. In the present study, we aimed to understand the contribution of the meningeal lymphatic system to ICH pathologies and to test whether pharmacological enhancement of meningeal lymphatic function promotes hematoma resolution and brain recovery after ICH. Immunofluorescence of whole-mount meninges was used to measure complexity and coverage level of meningeal lymphatic vasculature following ICH induction. Fluorescent microbeads and PKH-26-labeled erythrocytes were used to evaluate drainage function of the meningeal lymphatic system. Visudyne treatment, deep cervical lymph node ligation, and VEGF (vascular endothelial growth factor)-C injection were performed to manipulate meningeal lymphatic function. Neurobehavioral performance and hematoma volume were assayed by the cylinder test and histological measurements. Iron deposition, residual erythrocytes, neuronal loss, and astrogliosis were assessed by immunohistochemistry and antibody-based fluorescence staining. Meningeal lymphangiogenesis and enhanced lymphatic drainage occurred during the late phase of ICH. Ablation and blockage of meningeal lymphatic vessels impeded hematoma clearance, whereas pharmacological enhancement of their function reduced hematoma volume, improved behavioral performance, and reduced brain residual erythrocytes, iron deposition, neuronal loss, and astroglial activation. Early enhancement of meningeal lymphatic function is beneficial for ICH recovery. Targeting the meningeal lymphatic system is therefore a potential therapeutic approach for treating ICH.